KEBIASAAN MENONTON VLOG DIARI DAN KORELASI TERHADAP KETERAMPILAN RETORIKA MAHASISWA (Habits of Watching Vlog Diary and the Correlation to the College Student’s Rhetoric Skills) - Nini Ibrahim; Ummul Qura; Nur Amalia (SAWERIGADING, 2022)
Rhetoric skills are important for students. Through rhetoric, students can convey a purpose and objective persuasively. Students' rhetorical skills can be developed through the habit of watching vlog diaries. By doing the habit of watching diary vlogs, it is hoped that it will affect students' rhetorical skills. The purpose of this study was to find out whether or not there was a relationship between the habit of watching diary vlogs and rhetorical skills in Postgraduate students of the UHAMKA Indonesian Language Education Masters Program. This research uses quantitative research with cross sectional method. Test (Chi-Square) used found the PValue value of 0.043, meaning that this 0.043 value alpha (0.05) with the results of the odds ratio (OP) obtained 0.043 with a range (0.079-2.066), which means that the habit of watching this vlog diary has potential 2 (double) strength will have to do with rhetorical skills. The conclusions that can be summarized in this study are that there is a moderate relationship between the habit of watching diary vlogs and rhetorical skills.